2010
DOI: 10.1007/s00420-010-0574-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and assessment of occupational arsenic exposure in copper- and steel-smelting workers in China

Abstract: Release of As dust produced in crude ore extracting and smelting is the main pollution source of As in copper smelter plant. The methylation capacity of As decreases with the increase in As exposure level, and skin damage caused by As is associated with decreasing methylation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Arsenic methylation indices were defined as the percentages of respective arsenic species in urine samples. Moreover, PMI was calculated as (MMA+DMA)/ TAs and SMI as DMA/(MMA+DMA) [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic methylation indices were defined as the percentages of respective arsenic species in urine samples. Moreover, PMI was calculated as (MMA+DMA)/ TAs and SMI as DMA/(MMA+DMA) [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigations suggest that MMA III and DMA III are more toxic than iAs arsenite [24,25]. Urinary arsenic speciation is typically used as an indicator of arsenic metabolism in evaluating arsenic methylation capacity [26] in terms of the primary methylation index (PMI, defined as (MMA+DMA)/total arsenic (TAs)) and secondary methylation index (SMI, defined as DMA/(MMA+DMA)) [20,27]. Numerous epidemiological studies have revealed that the risk of adverse health effects is associated with arsenic methylation capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Dye production and use; clinical laboratories [220,247] Group 1 [76] 1 Not all of them are to be referred to group Non-infective risk As 7440-38-2 Timber manufacturing; pesticide use; As extraction industry; lead processing; pharmaceutical industry; glass industry; leather preservatives; antifouling paints; agrochemical production; microelectronics and optical industries; non-ferrous metal smelters; coal-fired power plants [254][255][256][257][258] Group 1 [263] Cd 7440-43-9 Cd mining; manufacturing of Cd-containing ores and products; Ni-Cd battery manufacturing, Cd alloy production [275,277,278] Group 1 [263] As: Arsenic; Cd: Cadmium; IARC: International Agency for Research on Cancer; CAS No. : Chemical abstract service number.…”
Section: -87-5mentioning
confidence: 99%
“…The workers in mechanical industries are exposed to the risk of illness from dyes, chemicals and glass [253][254][255][256][257][258] . After oral intake and gastrointestinal absorption, it is metabolized in the liver where it is conjugated with glutathione and methylated [259,260] .…”
Section: Arsenicmentioning
confidence: 99%
“…However, occupational inhalation exposure to airborne arsenic remains a serious health issue in some localities. A recent study reported that copper smelter workers in northeastern China were exposed to airborne arsenic values that were up to 57% above the short-term exposure threshold limit value of 20 µg·m −3 [230]. Seven of the 38 copper smelter workers selected for investigation had arsenic-related skin disorders including hyperkeratosis and/or hyper-pigmentation, as well as elevated urinary arsenic levels [230].…”
Section: Known Occupational Exposuresmentioning
confidence: 99%